International student motivations and experiences of studying in small to mid-sized universities in remote Canada: A scoping review - Yuan, Xuechen; Okonufua, Osagie; Kiani, Muhammad (Journal of International Students, 2025)
Canada is undergoing significant changes in its immigration policies to reduce the number of study permits and educational pathways for immigration; thus, understanding the realities of small- to mid-sized universities in remote regions potentially affected by this shift is imperative. However, international student motivations and experiences in these contexts remain underexplored in the literature. This scoping review investigates 21 English-language studies conducted in Canadian universities with student enrollment under 20,000, which examine international students’ push‒pull dynamics, lived experiences, and postgraduate retention. Key pull factors include postgraduate immigration pathways, English and cultural immersion, perceptions of safety and affordability, and inclusive school admission; meanwhile, academic pressure, parental expectations, and career-related concerns are major push factors. For lived experiences, recurring themes emerged, encompassing areas such as cultural adjustment, social attachment, language learning, institutional support, and systemic challenges—all of which shape decisions to remain or relocate after graduation.